2015
DOI: 10.1002/jsfa.7206
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of portal‐drained viscera to heat production in Iberian gilts fed a low‐protein diet: comparison to Landrace

Abstract: In spite of the low energetic efficiency and growth rate of Iberian compared to modern breeds, the contribution of PDV energy expenditure relative to THP was lower in Iberian compared to Landrace gilts in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 54 publications
(79 reference statements)
8
17
3
Order By: Relevance
“…Anderson et al pointed out that in pigs the haematocrit value was variable. Nonetheless, in previous studies also with Iberian pigs, similar values to those in the present study were found, ranging from 30 to 31% . The haematocrit value was higher in Iberian than in improved breeds, although some authors reported similar values in modern breeds to those reported herein …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Anderson et al pointed out that in pigs the haematocrit value was variable. Nonetheless, in previous studies also with Iberian pigs, similar values to those in the present study were found, ranging from 30 to 31% . The haematocrit value was higher in Iberian than in improved breeds, although some authors reported similar values in modern breeds to those reported herein …”
Section: Discussionsupporting
confidence: 91%
“…When the results obtained in the present study were compared with those of studies performed under like conditions, the preprandial PBF value was similar or in the lower range of data for modern breeds in the literature and in the same range of data obtained with Iberian pigs . Postprandial reduction of PBF elicited by betaine and CLA has not been reported previously.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations